Female Neighbors, Test Scores, and Careers - Sofoklis Goulas; Rigissa Megalokonomou; Yi Zhang (Center for Economic Studies and ifo Institute (CESifo), 2022)
How much does your neighbor impact your test scores and career? In this paper, we examine how an observable characteristic of same-age neighbors – their gender – affects a variety of high school and university outcomes. We exploit randomness in the gender composition of local cohorts at birth from one year to the next. In a setting in which school assignment is based on proximity to residential address, we define as neighbors all same-cohort peers who attend neighboring schools. Using new administrative data for the universe of students in consecutive cohorts in Greece, we find that a higher share of female neighbors improves both male and female students' high school and university outcomes. We also find that female students are more likely to enroll in STEM degrees and target more lucrative occupations when they are exposed to a higher share of female neighbors. We collect rich qualitative geographic data on communal spaces (e.g., churches, libraries, parks, Scouts and sports fields) to understand whether access to spaces of social interaction drives neighbor effects. We find that communal facilities amplify neighbor effects among females.
Keywords: J16; J24; I24; I26; 330; neighbour gender peer effects; cohort-to-cohort random variation; birth gender composition; geodata; STEM university degrees